Synthesis and characterization of tin based hybrid nanofibers and nanoflowers as photoelectrode in dye-sensitized solar cells - Bakr, Zinab Hassanien Hassanien (2019)
Photoanode plays a crucial role in the operation of dye-sensitized solar cells due to its many functions: (1) provide a surface for the adsorption of the dye and (2) accepts photoinjected electrons from the excited dye and conducts them to the external circuit to produce an electric current. The research embodied in this thesis describes the synthesis of composite metal oxides nanostructure as well as pure binary metal oxides and evaluate their suitability as a photoanode in the dye-sensitized solar cells. Due to the advantageous properties such as favorable conduction band level of TiO2/ZnO, high electron mobility (150 cm2 V-1 s-1 for nanocrystals) and high electrical conductivity of SnO2, attention is devoted to these three materials. Composite metal oxides in the SnO2-TiO2 and SnO2-ZnO nanostructures are chosen for the current work to overcome the limitation of the single metal oxide; such as low conduction band edge of SnO2, low charge mobility of TiO2 and lack of stability of ZnO based photoanode in dye-sensitized solar cells. Electrospinning method is adopted for the synthesis of composite nanostructures morphologies due to the feasibility of this method for developing nanoscale materials in large scales. The composites formation is confirmed by X-ray diffraction, energy dispersive X-ray and X-ray photoelectron spectroscopy analyses. The morphology is examined by field emission scanning electron microscopy and transmission electron microscopy with selected area electron diffraction. Morphological studies show that SnO2-TiO2 formed in two structures, nanofibers and nanoflowers by adjusting the precursor’s concentration whereas SnO2-ZnO gave nanofibers morphology. Synergy in the optical, electronic and electrical properties of the composite nanofibers is demonstrated by cyclic voltammetry, Mott-Schottky, and absorption spectroscopy. Current-voltage, Open-circuit voltage decay and electrochemical impedance measurements revealed that the composite nanostructures offering valuable properties when utilized as a photoanode in dye-sensitized solar cells in terms of photoconversion efficiency (PCE ~5.65% for SnO2-ZnO composite nanofibers, 7.40% for SnO2-TiO2 composite nanoflowers and ~8.50% for SnO2-TiO2 composite nanofibers) compared to its binary counterparts SnO2 (~3.90%), ZnO (~1.38%) and TiO2 nanofibers (~5.10%). Results of this research revealed a facile and scalable method to fabricate a simple composite electrode design for enhancing the functional performances of the final device.